Empowerment of Mekar Jaya Farmer Group through Eco Farming and Digital Marketing for Optimization of Coconut and Corn Diversification Products: Pemberdayaan Kelompok Tani Mekar Jaya melalui Ecofarming dan Digital Marketing untuk Optimalisasi Produk Diversifikasi Kelapa dan Jagung - Febriyanti Febriyanti; Novri Youla Kandowangko; Arif Dwinanto; Iswanto Bakari; Miftahul F. Adudu; Adila Nindhaulhasanah (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
The Mekar Jaya Farmers Group has great potential in utilizing coconut and corn for diversification of value-added products. However, limited knowledge of environmentally friendly agricultural techniques (Ecofarming) and access to digital marketing are the main obstacles in optimizing coconut and corn diversification products. This community partnership program (PKM) aims to empower the Mekar Jaya Farmers Group through the application of ecofarming methods and the introduction of digital marketing strategies to increase productivity and the selling value of diversified products. Activities include education and training in making organic fertilizers, managing organic waste, diversification of coconut and corn waste products such as cocopeat, cocofiber, and corn-based snacks, as well as assistance in using digital platforms for marketing. The results of the activities showed an increase in the understanding and skills of the Mekar Jaya Farmers Group regarding ecofarming practices by 85%, diversification of coconut waste products (80%), diversification of corn (75%) and the reach of product marketing through digital media increased by 70%. This program not only provides new understanding to farmers about the importance of sustainable agricultural practices, but also opens up wider opportunities in marketing their products through digital technology. The implementation of ecofarming, which maintains environmental sustainability, and the use of digital marketing , coconut and corn-based diversified products now have higher competitiveness in the market and are able to support the optimization of agricultural products as well as environmental sustainability.